2009
DOI: 10.1177/0893318909352248
|View full text |Cite
|
Sign up to set email alerts
|

Endorsing Equity and Applauding Stay-at-Home Moms: How Male Voices on Work-Life Reveal Aversive Sexism and Flickers of Transformation

Abstract: What can we learn about women’s organizational challenges by talking to men about gender roles and work-life? We attend to this question through an interview study with male executives, providing a close interpretive analysis of their talk about employees, wives, children, the division of domestic labor, and work-life policy. The study illustrates how executives’ tacit hesitancy about women’s participation in organizational life is closely connected to preferred gendered relationships in the private sphere. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 61 publications
(70 reference statements)
11
82
0
1
Order By: Relevance
“…Most family-friendly policies either explicitly or implicitly target mothers. Evidence suggests 'fatherhood' is perceived as irrelevant by line managers, and persistent manager and organisational attitudes about gendered roles constrain fathers' capacity to optimally balance work and care (13,38). Fathers are much less likely to request flexibility or part-time work even when provided (39)(40)(41), and there are measurable career and income detriments for fathers who do request these changes (37,42).…”
Section: The Work-family Interfacementioning
confidence: 96%
“…Most family-friendly policies either explicitly or implicitly target mothers. Evidence suggests 'fatherhood' is perceived as irrelevant by line managers, and persistent manager and organisational attitudes about gendered roles constrain fathers' capacity to optimally balance work and care (13,38). Fathers are much less likely to request flexibility or part-time work even when provided (39)(40)(41), and there are measurable career and income detriments for fathers who do request these changes (37,42).…”
Section: The Work-family Interfacementioning
confidence: 96%
“…More recently, Holter (2007) and Tracy and Rivera (2010) re-emphasize continuing resistance to involved paternity within organizational settings where masculinity is associated with high work orientation (Holter, 2007). They argue that despite 21st century trends towards relationship breakdown and single parenthood, alongside women's increased labour market participation, organizational classifications of men as belonging within the instrumental, economic provider group remain stable.…”
Section: Fathers As 'Instrumental' Economic Providersmentioning
confidence: 99%
“…While this apparent neglect of paternal child orientation has been linked in part to historic, gendered (and increasingly inaccurate) organizational views about parenting practices (Miller, 2011), reasons why fathers should still be marginalized within work−life balance initiatives remain unclear (Burnett et al, 2013). While lack of paternal access to flexible work has been the subject of prior theorizing (see for example Holter, 2007;Tracy and Rivera, 2010), relationships between mothers, fathers and employment remain hard to disentangle. In the context of gendered inequalities, limited research exists comparing how fathers perceive and experience access to flexible working in comparison with mothers, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the United States, for example, have shown that managers who have directly benefitted from family-friendly policies are more likely to endorse them in their own organizations than those who have not benefitted from such policies. For instance, executives who have had stay-at-home wives were less likely to endorse family-friendly policies than those who have had working wives (Tracy and Rivera 2010). Nonetheless, employer-initiated solutions are worthy of consideration in sub-Saharan Africa where they are yet to be developed.…”
Section: Employer-initiated Solutionsmentioning
confidence: 99%